The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/nph.14660
|View full text |Cite
|
Sign up to set email alerts
|

Type III metacaspases: calcium‐dependent activity proposes new function for the p10 domain

Abstract: Metacaspases are a subgroup of caspase homologues represented in bacteria, algae and plants. Although type I and type II metacaspases are present in plants, recently discovered and uncharacterized type III metacaspases can only be found in algae which have undergone secondary endosymbiosis. We analysed the expression levels of all 13 caspase homologues in the cryptophyte Guillardia theta in vivo and biochemically characterized its only type III metacaspase, GtMC2, in vitro. Type III metacaspase GtMC2 was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…A large number of metacaspases‐like genes are common in diazotrophic filamentous cyanobacteria. Nine metacaspases are found in Anabaena variabilis ATCC 29413, nine in Nostoc punctiforme while in the T. erythraeum IMS101 genome 12 TeMC have been identified (Jiang et al ., ; Asplund‐Samuelsson, ; Klemenčič and Funk, ); cumulatively representing 0.22% of total encoded proteome (Jiang et al ., ). We analysed the domain structures of the 12 TeMC proteins provide to additional context to their secondary structure and obtain possible clues for their cellular function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of metacaspases‐like genes are common in diazotrophic filamentous cyanobacteria. Nine metacaspases are found in Anabaena variabilis ATCC 29413, nine in Nostoc punctiforme while in the T. erythraeum IMS101 genome 12 TeMC have been identified (Jiang et al ., ; Asplund‐Samuelsson, ; Klemenčič and Funk, ); cumulatively representing 0.22% of total encoded proteome (Jiang et al ., ). We analysed the domain structures of the 12 TeMC proteins provide to additional context to their secondary structure and obtain possible clues for their cellular function.…”
Section: Resultsmentioning
confidence: 99%
“…The highest number of metacaspases from all cyanobacteria analysed to date are found in the marine diazotrophic Trichodesmium genome which contains 12 metacaspases (Jiang et al ., ; Asplund‐Samuelsson et al ., ; ). Due to the lack of the P10 domain in their sequence, metacaspases in prokaryotes are termed metacaspase‐like proteins or at other times orthocaspases (Choi and Berges, ; Klemenčič et al ., ; Klemenčič and Funk, ). Here, we use the term TeMC to describe Trichodesmium metacaspase‐like (TeMC) proteases.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, caspases are regulated through the post‐translational regulation of their activity as many of these genes are constitutively expressed (Fuentes‐Prior and Salvesen, ). When whole‐genome sequences became available over the past two decades, it was apparent that caspases have evolved specifically in the animal kingdom, and structurally related proteases called metacaspases (MCs) exist in other phyla that extend back to single‐cell eukaryotes, such as microalgae and fungi (Tsiatsiani et al ., ; Klemencic and Funk, ). Related genes encoding metacaspase‐like proteases with a conserved p20 domain that has catalytic motifs related to MCs have also been identified in sequenced genomes of many eubacteria and archaea, thus implicating their evolution from prokaryotic ancestors (Asplund‐Samuelsson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the results from loss‐of‐function analysis with several MC‐encoding genes in yeast and plants are consistent with their role in regulating PCD and stress responses, analogous to the case of caspases in animals, there are also interesting distinctions found between them. One key difference is that all three types of MCs that have been identified and characterized prefer target sites with a basic amino acid residue (arginine or lysine) at the P1 position instead of an aspartate, as in the case for caspases (Vercammen et al ., ; Zhang and Lam, ; Klemencic and Funk, ). Structural studies of type‐I MCs from yeast and protozoa also demonstrated that these enzymes function as monomers instead of dimers in the case of caspases (McLuskey et al ., ; Wong et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…As the regulatory modes of type I and II metacaspases are uncovered, the development of sequencing technologies gives access to genes encoding other types of metacaspases in other organisms. For example, through a bioinformatic analysis, Klemenčič & Funk (in this issue, pp. 1179–1191) discuss a type III metacaspase, named GtMC2, in the cryptophyte Guillardia theta .…”
mentioning
confidence: 98%